Synthesis, characterization and adsorption study of C-4-phenacyloxy-phenylcalix[4]resorcinarene for Pb(II), Cd(II) and Cr(III) ions - Rastuti, Undri; Siswanta, Dwi; Pambudi, Wisnu; Nurohmah, Beta Achromi; Bohari M. Yamin,; Jumina, (Penerbit Universiti Kebangsaan Malaysia, 2018)
C-4-phenacyloxy phenyl calix[4]resorcinarene (CPPCR) was synthesized by acidic condensation of 4-hydroxybenzaldehyde and resorcinol. The adsorption of CPPCR for Pb(II), Cd(II) and Cr(III) has been studied by measuring the metal concentration in aqueous solution using Atomic Absorption Spectrophotometry (AAS). The effects of solution pH, contact time and initial concentration of metal ions on the adsorption capacity of CPPCR were investigated. The adsorption kinetic of all the ions obeyed the Ho and McKay pseudo 2nd order rate law and the adsorption isotherm profile matched very well with Langmuir model. The separation factor (RL) of CPPCR for Pb(II), Cd(II) and Cr(III) were 0.190, 0.017, and 0.065, respectively, indicating the formation of monolayer behaviour. The Gibb free energy (ΔG) of the adsorption for all the metal ions have negative values indicating the adsorption process of Pb(II), Cd(II) and Cr(III) by CPPCR are spontaneous.